Social Cohesion and Community Resilience During COVID-19 and Pandemics: A Rapid Scoping Review to Inform the United Nations Research Roadmap for COVID-19 Recovery. (July 2021) - Jewett, Rae L.; Mah, Sarah M.; Howell, Nicholas; Larsen, Mandi M.
Shock events uncover deficits in social cohesion and exacerbate existing social inequalities at the household, community, local, regional, and national levels. National and regional government recovery planning requires careful stakeholder engagement that centers on marginalized people, particularly women and marginalized community leaders. The aim of this rapid scoping review was to inform the United Nations Research Roadmap for the COVID-19 Recovery, based on Pillar 5 of the United Nations Framework for the Immediate Socioeconomic Response to COVID-19: Social Cohesion and Community Resilience. We present a summary of key concepts across the literature that helped situate this review. The results include a description of the state of the science and a review of themes identified as being crucial to sustainable and equitable recovery planning by the United Nations. The role of social cohesion during a disaster, particularly its importance for upstream planning and relationship building before a disaster occurs, is not well understood and is a promising area of future research. Understanding the applicability of social cohesion measurement methodologies and outcomes across different communities and geographies, as well as the development of new and relevant instruments and techniques, is urgently needed in the context of the global COVID-19 pandemic.